SIKAP PEMIRSA TERHADAP MOTTO LIPUTAN 6 PETANG SCTV:AKTUAL, TAJAM, TERPERCAYA - alkatiri alkatiri (Jurnal Sosial Humaniora, 2011)
The present research is aimed to: 1. identify individual perception or attitudes towards ’Liputan 6 Petang SCTV’, a news program with its motto: actual, critical and trustworthy. (2) identify the interrelation between individual characteristic with audiences’ opinions towards the motto of actual, critical and trustworthy (3) identify relationship between communication attitudes and broadcasting design towards audiences’ opinion on the Liputan 6 Petang’s motto of actual, critical and trustworthy (4) identify attitudes and reactions with audiences’ opinion towards the Liputan 6 Petang’s motto of actual, critical and trustworthy. This research utilizes correlation description research method and 150 samples. A number of variables that measured including respondents’ characteristics, communications attitudes, broadcasting design, audiences’ opinions towards Liputan 6 Petang’s motto, as well as audiences’ reaction after viewing Liputan 6 Petang. Data were analysed based on Spearman correlation coefficient. Research findings show that: 1. there is a correlation between audiences’ characteristics in Jabotabek region with some parts of opinions of Liputan 6 Petang’s motto. 2. There is a significant correlation between audiences’ communication attitudes towards Liputan 6 Petang’s motto 3. In general there is a correlation between program design with Jabotabek audiences’ opinion towards Liputan 6 Petang’s motto. 4. There is a significant correlation a part of audiences’ opinions towards Liputan 6 Petang SCTV with audiences’ attitudes and reactions.